PERTANGGUNGJAWABAN PIDANA PENYIMPAN VIDEO PORNO: ANTARA NORMA KESUSILAAN DAN HAK PRIVASI BERDASARKAN UNDANG-UNDANG REPUBLIK INDONESIA NOMOR 44 TAHUN 2008 TENTANG PORNOGRAFI - Handoko, Aji; Sari, Indah (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2024)
This study examines the criminal liability of pornographic video depositors in Indonesia, by considering aspects of decency norms and privacy rights based on Law Number 44/2008 on Pornography. This study uses normative legal research method with statutory and conceptual approaches. The results show that there is a tension between efforts to uphold the norms of decency through the criminalisation of ownership of pornographic material and the protection of individual privacy rights. The Pornography Law has not expressly regulated criminal liability for storing pornographic videos for personal consumption, creating legal ambiguity. This research recommends the need for revision of the law to provide legal clarity, taking into account the balance between public interest and privacy rights, and adopting a more proportional approach in determining criminal sanctions.